AN APPRAISAL OF THE CONSTITUTIONAL AND REGULATORY MECHANISMS FOR THE APPOINTMENT OF JUDICIAL OFFICERS IN NIGERIA AND ASSOCIATED CHALLENGES (UUM Journal of Legal Studies, 2020)
The institution to settle the dispute between individuals is a court of law manned by Judges. To nominate and appoint the judges are herculean tasks which involve processes to ensure only fit and proper persons occupy Judicial Offices. This paper examined the constitutional and regulatory procedures for the appointment of Judicial Officers in Nigeria. The study identified the problems associated with the processes of the appointment of the Judicial Officers in Nigeria. The work adopted the socio-legal research method by using the qualitative approach. There is a dearth of literature in Nigeria on how the procedure for the appointment of Judicial Officers operates practically and the real problems associated with the operation of the procedural laws. To achieve the research objectives, a semi-structured interview was used. Three specialists in the Nigerian legal profession were interviewed to find out the actual issues on the ground. The study discovered that lobbying has been entrenched in the process of the appointment of Judicial Officers in Nigeria. The research further found that the powers of the Chief Justice of Nigeria to appoint the majority of members of the recommendation body threatens the independence of the Judiciary.